Immunomodulatory activities associated with beta-glucan derived from Saccharomyces cerevisiae - Pelizon, A. C. (2005)
In this study we investigated the effect of beta-glucan derived from Saccharomyces cerevisiae on fungicidal activity, cytokine production and natural killer activity. Spleen and peritoneal cells from female C57BL/6 mice, previously injected (24 or 48 h) with 20 or 100 mu g of glucan by i.p. route, were assayed. In vivo mu-glucan administration primed spleen cells for a higher production of IL-12 and TNF-alpha when S. aureus was used as a stimulus. In addition, beta-glucan increased NK spleen cells activity against YAC target cells. Some immunomodulatory activities not yet described for beta-glucan were observed in this work.